Matrilinealitas dan Representasi Politik Perempuan: (Analisis Rendahnya Representasi Politik Perempuan di DPRD Kabupaten Pasaman Barat pada Pemilu 2024) - Dela Ayunda Respita; Mariatul Qibtiyah; M Wira Anshori (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
In the Minangkabau social system, women hold a crucial position as owners of lineage and inherited property. However, in formal political practice, women's representation in legislative institutions remains relatively low. This study uses a qualitative approach, collecting data through interviews, documentation, and literature review. The results indicate that despite the affirmative action policy of a 30 percent quota for women in legislative candidacy, the representation of elected women remains limited. This is influenced by several factors, including patriarchal culture in local politics, limited political resources for women, and low political party support for female candidates. These findings suggest that the matrilineal system does not automatically result in equal political representation for women in legislative institutions. Therefore, strengthening women's political capacity and ensuring political party commitment to encouraging increased women's representation in legislative institutions is necessary. This study aims to analyze the low political representation of women in the West Pasaman Regency legislative institution in the 2024 General Election.